2014
DOI: 10.1007/s10340-014-0558-6
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Thaumastocoris peregrinus in Eucalyptus plantations of South Africa

Abstract: Thaumastocoris peregrinus is a sap sucking insect that infests non-native Eucalyptus plantations in Africa, New Zealand, South America and parts of Southern Europe, in addition to street trees in parts of its native range of Australia. In South Africa, pronounced fluctuations in the population densities have been observed. To characterise spatiotemporal variability in T. peregrinus abundance and the factors that might influence it, we monitored adult population densities at six sites in the main eucalypt growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
0
14
2
1
Order By: Relevance
“…Nadel et al (), in their work on population dynamics of T. peregrinus, found that the temperature range tolerated by this insect was between 4 and 39°C, being 30°C the optimum for egg development. Most of the isolates exhibited high spore viability at 30°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nadel et al (), in their work on population dynamics of T. peregrinus, found that the temperature range tolerated by this insect was between 4 and 39°C, being 30°C the optimum for egg development. Most of the isolates exhibited high spore viability at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…isolates, those were selected to assess viability at different temperatures and water activity, as these parameters can correlate with suitability for field applications in suboptimal conditions. Nadel et al (2015), in their work on population dynamics of T. peregrinus, found that the temperature range tolerated by this insect was between 4 and 39°C, being 30°C the optimum for egg development. Most of the isolates exhibited high spore viability at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…These results may explain the population outbreaks that occur during the hot summer season. The maximum critical thermal range for T. peregrinus adults was identified as between 32 and 45 °C by Nadel et al () who reported a mean maximum critical thermal value of 38.6 ± 4.7 °C. Our results showed that high temperatures became limiting at some point between 30 and 35 °C, although the methodology used in the present study was quite different from that in Nadel et al ().…”
Section: Discussionmentioning
confidence: 99%
“…and hybrids in Brazil, where the effect of host species on the life cycle and reproduction of T. peregrinus was demonstrated. More recently, Nadel et al () conducted a study on the population dynamics of this pest in Eucalyptus plantations of South Africa, as well as laboratory experiments aiming to determine the influence of temperature on growth and survival.…”
Section: Introductionmentioning
confidence: 99%
“…It has a short life cycle (an average of 35 days) and the female can lay up to 60 eggs during her lifespan (Jacobs and Neser, 2005;Noack and Rose, 2007;Soliman et al, 2012). This high biotic potential enables T. peregrinus to have several generations per year, and to have the potential to spread and rapidly establish into new environments (Nadel et al, 2015;Saavedra et al, 2015).…”
Section: Introductionmentioning
confidence: 99%